ALGORITHMS FOR DIAGNOSTIC AND PARAMETER OF FAILURES OF CHANNELS OF MEASUREMENT OF TV3-117 AIRCRAFT ENGINE AUTOMATIC CONTROL SYSTEM IN FLIGHT MODES BASED ON NEURAL NETWORK TECHNOLOGIES - Vladov, Serhii (Proceedings of National Aviation University (archive), 2020)
The solution of the reliability increasing problem of the TV3-117 aircraft engine automatic control system (ACS) through the use of the algorithmic redundancy is offered. The purpose of research is development of algorithms of measuring channels’ fault diagnostics and counteraction for input parameters of linear adaptive on-board engine model (LABEM) built into the ACS. The LABEM basic mathematics is shown. The static model is based on the throttle characteristics of the individual engine. The throttle characteristics was obtained in the acceptance tests or "race" in the operation after the service. The lower level dynamic linear mathematical model of a gas-turbine engine is obtained by state space method. The technical and theoretical difficulties of practical implementation of algorithmic reservation by the model are associated with the high dimensionality of the engine state space, that are significantly higher than the dimension of the vector of parameters measured on board. There is a problem of identification of sensor fault with subsequent replacement of the value by modeling information. The necessity of fault detection and isolation algorithms in is justified. To improve the reliability of the fuel circuit input information the Kalman-filtering algorithms with integrated fault detection and isolation logic for the measuring channels are used. The fault detection and isolation algorithms for sensors’ channels measurement in dosing needle loop based on Kalman filters were described. The algorithms are based on the calculation of the fault signature as weighted sum of the squares of residuals (WSSR), which is compared with the selected threshold value. The practice results of engines’ stand tests and MatLab simulation showed the high reliability and quality of TV3-117 aircraft engine ACS based on proposed algorithms.